2007
DOI: 10.1002/micr.20376
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical nonmicrovascular flaps in forearm and hand reconstruction

Abstract: Relatively new method in flap's surgery, perforator flaps tends to monopolize nowadays the surgeon's interest. The question is: could these flaps be used not only as free flaps, as were mainly used until now, but also as local or regional flaps? On the basis of our experience with 115 operated cases, we will try to demonstrate that a lot of simple or composite defects in the forearm and hand could be covered, in selected cases, by using local or regional perforator flaps. This may have as result, in the future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 55 publications
1
95
1
Order By: Relevance
“…7 A perforator-based propeller flap can be designed on any perforator, and a number of articles present the usefulness of individual perforator-based flaps for upper limb reconstruction. 18,19,30,[35][36][37][38][39][40][41][42][43][44][45][46][47][48] The elbow, wrist, and hand represent the 3 areas in the upper limb that usually require flap reconstruction. The perforator flaps available for elbow reconstruction include 5 flaps: (1) inferior ulnar collateral artery perforator flap (IUCAP), 6,37,38 (2) SUCAP, 6,39,40 (3) BAP, 6,49,50 (4) RRAP, 6,51-53 and (5) RCAP.…”
Section: Discussionmentioning
confidence: 99%
“…7 A perforator-based propeller flap can be designed on any perforator, and a number of articles present the usefulness of individual perforator-based flaps for upper limb reconstruction. 18,19,30,[35][36][37][38][39][40][41][42][43][44][45][46][47][48] The elbow, wrist, and hand represent the 3 areas in the upper limb that usually require flap reconstruction. The perforator flaps available for elbow reconstruction include 5 flaps: (1) inferior ulnar collateral artery perforator flap (IUCAP), 6,37,38 (2) SUCAP, 6,39,40 (3) BAP, 6,49,50 (4) RRAP, 6,51-53 and (5) RCAP.…”
Section: Discussionmentioning
confidence: 99%
“…When the use of propeller flaps is not possible due to technical limits, the coverage of the defect should then be performed by means of perforator-based flaps with fascial pedicle or by local flaps with sacrifice of a major vascular bundle. The clinical experiences reported in the literatures [10, 17, 18] demonstrated that the propeller flaps can be employed with positive results in the upper limb for the treatment of traumatic loss of substances, as well as after tumor excisions, burns, and other conditions. In selected cases even complex defects may be treated with propeller flaps harvested as composite flaps.…”
Section: Discussionmentioning
confidence: 99%
“…The pedicle can be isolated by means of loupes and microscope is normally not required [8, 9]. Therefore, as reported by Georgescu et al, this local perforator flap that requires a microsurgical dissection without vascular sutures can be defined as a “microsurgical not microvascular flap” [10]. The absence of vascular sutures and the preservation of major vascular and underlying muscles are the main advantages of propeller flaps.…”
Section: Introductionmentioning
confidence: 99%
“…24 Some surgeons advocated that by suturing a subcutaneous vein, the risk of venous congestion can be reduced. 25 In our study series, we tended to utilize a conservative treatment that included massaging the flap, which resulted in a satisfactory result. The necrosis site was controlled by complimentary split thickness grafting 4 weeks later.…”
Section: Discussionmentioning
confidence: 96%